Extraction and purification of high added value compounds from by-products of the winemaking chain using alternative/nonconventional processes/technologies. Issue 8 (24th May 2018) - Yammine, Sami; Brianceau, Sylène; Manteau, Sébastien; Turk, Mohammad; Ghidossi, Rémy; Vorobiev, Eugène; Mietton-Peuchot, Martine
ABSTRACT: Grape byproducts are today considered as a cheap source of valuable compounds since existent technologies allow the recovery of target compounds and their recycling. The goal of the current article is to explore the different recovery stages used by both conventional and alternative techniques and processes. Alternative pre-treatments techniques reviewed are: ultrasounds, pulsed electric fields and high voltage discharges. In addition, nonconventional solvent extraction under high pressure, specifically, supercritical fluid extraction and subcritical water extraction are discussed. Finally alternative purification technologies, for example membrane processing were also examined. The intent is to describe the mechanisms involved by these alternative technologies and to summarize the work done on the improvement of the extraction process of phenolic compounds from winery by-products. With a focus on the developmental stage of each technology, highlighting the research need and challenges to be overcome for an industrial implementation of these unitary operations in the overall extraction process. A critical comparison of conventional and alternative techniques will be reviewed for ethe pre-treatment of raw material, the diffusion of polyphenols and the purification of these high added value compounds. This review intends to give the reader some key answers (costs, advantages, drawbacks) to help in the choice of alternative technologies for extraction purposes.